Nurses' Knowledge of Pain Management for Patients with Combat‐Related Traumatic Brain Injuries on Rehabilitation Units. Issue 2 (March 2015) - Jaimes, Lorena M.; Thompson, Hilaire J.; Landis, Carol A.; Warms, Catherine A.
Abstract : Purpose: : The purpose of this project was to survey nurses' knowledge of pain management for patients with combat‐related traumatic brain injuries (TBI). Design/Methods: : A survey was used to collect data regarding nurses' knowledge of pain assessment and management for patients with combat‐related TBI. Nurses were invited to participate in the study via email and provided with a link to the electronic survey. Findings: : Twenty‐five surveys were returned (52% response rate). A total of 76% of nurse respondents perceived that TBI patients over report pain intensity. Only 40% of nurses were able to correctly identify the appropriate medication to treat migraine‐type headache pain in TBI patients. Conclusion: : This study identified gaps in knowledge regarding pain management for patients with combat related TBIs. Clinical Relevance: : Nurses need additional education regarding common pain syndromes, available treatments, and a better understanding of addiction in order to provide optimal care to these patients.